Implementación de una infraestructura tecnológica para la conexión de switch´s en cascada con fibra óptica en el área de tic`s de la unidad de nivelación y admisión de la Universidad Técnica de Cotopaxi, ubicada en la ciudad de Latacunga provincia de Cotopaxi, en el período abril - agosto 2014 - Plasencia Caiza, Carina Natali (2016)
This work is based specifically on the studious needs of students from the Technical University of Cotopaxi , thus allowing us to optimize the technology infrastructure in the area of TIC`s of Equalization and Admission Unit also improve the speed of information transmission each of the computers installed in it, so that users will have greater ease of understanding in each of the explanations give the teacher and will implement each of the knowledge acquired in the classroom regarding what learn during their classes. The importance of this thesis was established that through the implementation of a technological infrastructure for connecting switch's cascaded optical fiber , we will improve the performance of bandwidth and learning about managing users fiberoptic internet and you will see the importance that this entails .